Impact of the Recitation Method to Improve Learning Outcomes in Arabic Language among Islamic Middle School - Muhamad Ihwanul Muslimin; Raswan Raswan; Imron Hamdani (Al-Muyassar: Journal of Arabic Education, 2024)
This study aims to assess the impact of a recitation learning method to improve Arabic language learning in Islamic Intermediate School. This search method uses an experimental design with a control group and an experimental set. The pilot group will apply the recitation learning method, while the control group will use the traditional learning method. Academic achievement data will be collected through the Arabic Proficiency Assessment Test and the structured evaluation of tasks. This research brought together the school's eighth-grade pupils out of 34, and appointed the researcher to 17 pupils as a pilot group and 17 as a control group. The researcher used data collection methods as direct observation, personal interview, tests and questionnaires. The data will be analysed using statistical techniques to compare the results of achievement between the two groups. It is hoped that this study will provide insight into the effectiveness of recitation learning method in improving students' understanding and learning Arabic in an integrated Islamic education environment. After analyzing the data, the researcher reached the two test averages: tribal and remote testing. Based on the average value of the experimental group on the value of the 78 and the average value of the control group on the value of the 71, the average value of the experimental group is greater than the control group's average value. I came up with the analysis of the data with the test rule "t" as a result of the calculation (t0) is 4, 5 the table is at the level of 5% indicator of the value of 1, 677 and the level of 1% indication of the value of 2, 408 this indicates that the zero hypothesis (h0) is returned and the alternative hypothesis (ha) is acceptable. This means that the use of a recitation learning method to improve educational access in Arabic language learning is statistically effective.